2015
DOI: 10.1007/s10495-015-1091-7
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the complement C5b-9 complex sensitizes 661W photoreceptor cells to both apoptosis and necroptosis

Abstract: The loss of photoreceptors is the defining characteristic of many retinal degenerative diseases, but the mechanisms that regulate photoreceptor cell death are not fully understood. Here we have used the 661W cone photoreceptor cell line to ask whether exposure to the terminal complement complex C5b-9 induces cell death and/or modulates the sensitivity of these cells to other cellular stressors. 661W cone photoreceptors were exposed to complete normal human serum following antibody blockade of CD59. Apoptosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…It is known that depositions of MAC on the cell membrane induces apoptosis (Sato et al, 1999; Hughes et al, 2000). Shi et al reported that MAC promoted apoptosis in their used cone photoreceptor cell line (Shi et al, 2015). In an OHT glaucoma model, the depletion of the complement system reduced apoptotic RGCs (Jha et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that depositions of MAC on the cell membrane induces apoptosis (Sato et al, 1999; Hughes et al, 2000). Shi et al reported that MAC promoted apoptosis in their used cone photoreceptor cell line (Shi et al, 2015). In an OHT glaucoma model, the depletion of the complement system reduced apoptotic RGCs (Jha et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This is different from the present study, in which 661W and RGC-5 cells developed an average of 3.0 ± 0.1 and 3.1 ± 0.3 primary neurites per cell, respectively, when exposed to 316 nM staurosporine, the concentration which was optimal for differentiation. [ 17 ]. It should be also noted that that study and the present study only assessed morphological features of neuronal differentiation, and a more extensive study of cell-surface markers and electrophysiological activity would be needed to confirm a neuronal phenotype, as was done previously [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the difficulty of isolation and culture of primary photoreceptor cells, a photoreceptor cell line 661W has been widely used to study mechanisms of photoreceptor dysfunction and degeneration, and develop strategies to protect photoreceptors in a variety of conditions such as light damage, retinitis pigmentosa, diabetic retinopathy, retinal dystrophy, and retinal detachment (Aslanidis et al, 2015;Besirli et al, 2012;Byrne et al, 2016;Du et al, 2015;Izawa et al, 2016;Jackson et al, 2016;Krishnamoorthy et al, 1999;Lee et al, 2016;Rapp et al, 2014;Scholz et al, 2015;Shi et al, 2015;Tan et al, 2004;Zhang et al, 2014). To determine whether photoreceptor cells can produce chemokines CXCL10 and CCL2 under stress conditions, we treated 661W cells with thapsigargin (TG), which potently induces ER stress at 0.01-0.1 μM (Bartolome et al, 2012;Hamamura and Yokota, 2007) and is widely used to study ER stress-induced cellular responses (Bartolome et al, 2012;Hamamura and Yokota, 2007;Kim et al, 2008).…”
Section: Endoplasmic Reticulum (Er) Stress Induces Cxcl10 and Ccl2 Prmentioning
confidence: 99%